2019
DOI: 10.1055/s-0039-1688908
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Outcomes with Detoxification from Opioid Drugs during Pregnancy: A Systematic Review

Abstract: Objective This study aimed to perform a systematic review of all studies reporting fetal outcomes following detoxification or tapering of opioid drugs during pregnancy. Study Design PubMed, Scopus, Medline, and Google Scholar were searched, and only manuscripts clearly reporting pregnancy/fetal outcomes involving tapering or detoxification from opioid drugs were included. Only pregnancies managed after 1980 were included (when antenatal fetal surveillance became more routine). Collected data includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…4,31,32 Multiple subsequent studies have established that these risks were likely overstated, and recent systematic reviews have not demonstrated any increased risk of poor fetal outcome from tapering or detoxification in pregnancy. 33,34 Our findings further support that historic concerns regarding naloxone exposure in pregnancy are unfounded and should not drive MAT choice today. The pharmacokinetics of naloxone are such that following oral ingestion and metabolism, the drug remains inactive; however, intravenous or intramuscular injection will precipitate withdrawal.…”
Section: Comparison With Existing Literaturesupporting
confidence: 61%
“…4,31,32 Multiple subsequent studies have established that these risks were likely overstated, and recent systematic reviews have not demonstrated any increased risk of poor fetal outcome from tapering or detoxification in pregnancy. 33,34 Our findings further support that historic concerns regarding naloxone exposure in pregnancy are unfounded and should not drive MAT choice today. The pharmacokinetics of naloxone are such that following oral ingestion and metabolism, the drug remains inactive; however, intravenous or intramuscular injection will precipitate withdrawal.…”
Section: Comparison With Existing Literaturesupporting
confidence: 61%
“…Two systematic reviews and a meta-analysis failed to find the previously expected increase in negative outcomes in children, such as miscarriage, preterm births, reduced birth weight, and NAS, after tapering or detoxification relative to children born of women with continued use of opioids (Terplan et al, 2018;Towers et al, 2020;M. Wang et al, 2018).…”
Section: Medically Assisted Treatment During Pregnancymentioning
confidence: 96%
“…Thus, a major concern has been maternal overdose and death after detoxification, as occurred postpartum for two women in an early study (Blinick et al, 1969). However, contemporary studies have not documented maternal death from detoxification during pregnancy; none were found in a structured review of 14 studies of opioid detoxification or tapering during pregnancy (Towers et al, 2020).…”
Section: Medically Assisted Treatment During Pregnancymentioning
confidence: 99%
“…Medically supervised opioid withdrawal or detoxification in pregnant women with OUD is possible and has been suggested as an important strategy to decrease fetal exposure and opioidassociated fetal brain stress, [31][32][33][34][35][36][37][38] but needs to account for the possibility of maternal relapse and fetal withdrawals, which may result in fetal demise. 39 Rather, because it significantly reduces the risk of both relapse and withdrawal, MAT is the preferred treatment modality for pregnant women with OUD.…”
Section: Mats In the Pregnant Woman With Oudmentioning
confidence: 99%